Dielectron production at midrapidity at low transverse momentum in peripheral and semi-peripheral Pb–Pb collisions at √ˢɴɴ = 5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Springer Science and Business Media Deutschland GmbH, 2023)
The first measurement of the e⁺e⁻ pair production at low lepton pair transverse momentum (Pᴛ,ₑₑ) and low invariant mass (mₑₑ) in non-central Pb–Pb collisions at √ˢɴɴ = 5.02TeV at the LHC is presented. The dielectron production is studied with the ALICE detector at midrapidity (|ɳe| < 0.8) as a function of invariant mass (0.4 ≤ mₑₑ < 2.7 GeV/c²) in the 50–70% and 70–90% centrality classes for Pᴛ,ₑₑ < 0.1 GeV/c, and as a function of Pᴛ,ₑₑ in three mₑₑ intervals in the most peripheral Pb–Pb collisions. Below a Pᴛ,ₑₑ of 0.1 GeV/c, a clear excess of e⁺e⁻ pairs is found compared to the expectations from known hadronic sources and predictions of thermal radiation from the medium. The mee excess spectra are reproduced, within uncertainties, by different predictions of the photon–photon production of dielectrons, where the photons originate from the extremely strong electromagnetic fields generated by the highly Lorentz-contracted Pb nuclei. Lowest-order quantum electrodynamic (QED) calculations, as well as a model that takes into account the impact-parameter dependence of the average transverse momentum of the photons, also provide a good description of the Pᴛ,ₑₑ spectra. The measured √⟨P²ᴛ,ₑₑ ⟩ of the excess Pᴛ,ₑₑ spectrum in peripheral Pb–Pb collisions is found to be comparable to the values observed previously at RHIC in a similar phase-space region.
Keywords: Jets and Jet Substructure, Quark-Gluon Plasma; https://purl.org/pe-repo/ocde/ford#1.03.03